Incidental Finding of Gastric Schwannoma in a Renal Failure Patient – Managed by a Minimally Invasive Procedure: Report of a Rare Case - Mujtaba, Mohamed A. (Am J Case Rep, 2019)
Patient: Female, 69 Final Diagnosis: Gastric Schwannoma Symptoms: Asymptomatic Medication: — Clinical Procedure: — Specialty: Gastroenterology and Hepatology OBJECTIVE: Rare co-existance of disease or pathology BACKGROUND: Schwannomas are benign tumors originating from any nerve with a Schwann cell sheath. It is an extremely rare tumor, accounting for 0.2% of all gastrointestinal tumors and 4% of all benign tumors of the stomach. Clinical differentiation of gastrointestinal mesenchymal tumors is challenging and confirmatory diagnosis requires biopsy. Surgical resection is the treatment of choice when tumor size is less than 30 mm or when it is located within the muscularis propria. Here, we present a case of a large (>50 mm) gastric Schwannoma that was resected using a new laparoscopic technique suitable for larger tumors. CASE REPORT: A 69-year-old woman with past medical history of hypertension, diabetes mellitus, and stroke, and CKD stage 4, presented to the Emergency Department (ED) with persistent nausea, vomiting, and weakness. She was found to have uremia requiring emergent hemodialysis. Eventually, she underwent peritoneal catheter insertion for peritoneal dialysis. A mass on the gastric antrum was found incidentally during the procedure. Biopsy confirmed the diagnosis of gastric Schwannoma. The tumor was removed successfully using a minimally invasive procedure via robotic-assisted laparoscopy. CONCLUSIONS: Gastric Schwannoma is a rare submucosal tumor arising from Auerbach’s plexus in the muscularis propria. It is usually asymptomatic, but can present with symptoms such as epigastric pain, or upper gastrointestinal bleeding. Tissue biopsy and immunohistochemical staining are the criterion standard for diagnosis. It has no tendency for malignant transformation. Tumors smaller than 30 mm are removed endoscopically, while tumors larger than 30 mm can be removed surgically. In this case, the tumor was removed successfully by minimally invasive robotic-assisted laparoscopy.